UPAYA DAKWAH JAM’IYYAH RUQYAH ASWAJA DI KECAMATAN BANGUNREJO TAHUN 2019-2020 - Khotimah, Amiyati Khusnul; Sabdo, Sabdo; Rohman, Fathur (DECODING: Jurnal Mahasiswa KPI, 2020)
Ruqyah is one of the treatment oldest methods on earth before medical development. At first, ruqyah is forbidden because it contains elements of shirk.However, after the arrival of Islam and the revelation of the Qur'an, the ruqyah treatmentmethod was adjusted to the Islamic Shari'a which was certainly far from the element ofshirk. So, ruqyah is allowed even recommended as in Surah Al-Isro 'verse 82. This undergraduate thesis is titled " The Da’wah Efforts of Jam'iyyah AswajaRuqyah in Bangunrejo Sub-District in 2019-2020". The formulas that are examined inthis thesis, 1.) How is the effort of Jam'iyyah Aswaja Ruqyah in Bangunrejo Sub-District?2) What changes in religious behaviour after the patient is in ruqyah? . For uncoveringthese problems in this study, it uses qualitative research methods by presentingdescriptive data. Taking informants is used purposive sampling. Da'wah efforts undertaken are by 1) socializing, distributing pamphlets and capturingcommunication with religious leaders and local communities. 2) practice, organizingmass treatment activities. 3) counselling, the approach used to find out your condition. 4)Da'wah, the Da'wah content messages are adjusted to the Mad'u condition for making itmore striking. (5) evaluation monitoring, to find out the da'wah success or failure. Theda'wah efforts were undertaken by Jam'iyyah Aswaja Ruqyah in preaching the Qur'an asan effective medicine was due to the obvious changes in religious behaviour experiencedby patients after ruqyah. The change was in the form of an increase in the value ofworship, wages of thought patterns, social interaction and is supported by physical andspiritual health that was getting better.